2022
DOI: 10.1007/978-3-030-99550-8_17
|View full text |Cite
|
Sign up to set email alerts
|

The Cerebellum and Disorders of Emotion

Abstract: Advances in Experimental Medicine and Biology provides a platform for scientific contributions in the main disciplines of the biomedicine and the life sciences. This series publishes thematic volumes on contemporary research in the areas of microbiology, immunology, neurosciences, biochemistry, biomedical engineering, genetics, physiology, and cancer research. Covering emerging topics and techniques in basic and clinical science, it brings together clinicians and researchers from various fields.Advances in Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 779 publications
0
3
0
Order By: Relevance
“…Some studies revealed that the DLPFC is strongly connected to frontal cortices that are preferentially involved in motor control [30]. FMRI studies frequently reported coactivation between the DLPFC and cerebellum during cognitive tasks [39][40][41]. Moreover, the application of repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS) to the DLPFC resulted in core symptom (emotion and cognition) improvement on major depression disorder (MDD) [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies revealed that the DLPFC is strongly connected to frontal cortices that are preferentially involved in motor control [30]. FMRI studies frequently reported coactivation between the DLPFC and cerebellum during cognitive tasks [39][40][41]. Moreover, the application of repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS) to the DLPFC resulted in core symptom (emotion and cognition) improvement on major depression disorder (MDD) [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…The anteroventral/anteromedial together with the mediodorsal nuclei play important roles in connecting subcortical limbic structures (amygdala) to the limbic cortex (anterior cingulate and orbitofrontal cortex) [ 56 ]. In addition, the cerebello–thalamo–cortical loops are implicated in emotion regulation and subjective sense of control [ 57 ]; and aberrant intrinsic FC of the thalamocortical pathway was associated with depression [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In support of the hypothesis of a cerebellar role in affective regulation, the occurring of both depressive and manic symptoms has recently been reported in patients with cerebellar disease of different etiology, creating a bridge between the two disorders ( Clausi et al, 2019 ; Lupo et al, 2019 ). Though, the interest in deepening the contribution of the cerebellum in BD brain networks has increased lately ( Argyropoulos et al, 2021 ; Olivito et al, 2022a ), promoted by the plethora of studies that are nowadays available about the anatomical and functional connections that link the cerebellum and subcortical limbic and cortical associative areas involved in emotional and affective regulation ( Stoodley and Schmahmann, 2009 ; Adamaszek et al, 2017 ; Baumann and Mattingley, 2022 ; Schutter, 2022 ). In BD, the persistence of functional connectivity changes during the euthymic phases has been reported.…”
Section: Introductionmentioning
confidence: 99%